Where have the enteric viruses gone? - Differential effects on frequent causes of infectious diarrhoea by SARS-CoV-2 pandemic lockdown measures. Issue 4 (December 2021) - Mack, Dietrich; Gohl, Peter; Kolbert, Mathias; Schui, Daniela; Küsters, Uta; Harzer, Oliver; Pum, Joachim; Zöllner, Bernhard
Summary: Background: Measures of distancing, wearing face/medical masks and lockdown introduced in many countries to meet the challenges of the SARS-CoV-2 pandemic have led to gross changes in the epidemiology of important infections. The observation of decline of positive norovirus tests after introduction of lockdown in Germany led us to investigate changes in the detection of major causes of diarrhoea by comparing pre-pandemic quarters (PPQ: 1Q/17 through 1Q/20) since 2017 and pandemic quarters (PQ: 2Q/20 through 1Q/21). Methods and setting: Bioscientia Laboratory Ingelheim is a large regional clinical pathology laboratory serving > 50 hospitals and > 5000 general practitioners and specialist outpatient practices located in the federal states Hesse, Rhineland-Palatinate and North Rhine-Westphalia, Germany. Antigen detection assays were used for detection of astrovirus, adenovirus, rotavirus, and Campylobacter antigen and Clostridium difficile Toxin A/B, while norovirus was detected by qualitative RT-PCR. Findings: The mean positivity-ratios of norovirus, adenovirus and astrovirus assays were 3–20 fold lower in periods PQ (2Q/20 through 1Q/21) compared to PPQ (1Q/17 through 1Q/20) (p<.01). The mean positivity-ratio was lower in PQ compared to PPQ for rotavirus (p=.31), but failed to reach statistical significance, while for campylobacter antigen (p=.91) and C. difficile Toxin A/B (p=.17) the mean positivity-ratio was even higher in PQ compared to PPQ. Conclusions: Apparently, hygienic measures used to contain the SARS-CoV-2 pandemic have differential effects on incidence of diarrhoea viruses as compared to bacterial gastrointestinal agents, particularly C. difficile, which may lead to re-evaluate measures implemented against this important cause of nosocomial diarrhoea.